PENGARUH LIVE STREAMING SHOPPING TERHADAP PENJUALAN BARANG THRIFSHOP DI KOTA BATAM: Live Streaming Shopping - Yohana Juwitasari Hulu; Renny Christiarini (JWM (JURNAL WAWASAN MANAJEMEN), 2023)
This research is based on the phenomenon of selling goods with live broadcasts on social media since the Covid-19 pandemic to know several factors that influence purchase intentions on live streaming shopping on the sale of used goods in Batam City. The study was conducted by collecting 330 samples obtained by distributing questionnaires to people who had watched live broadcasts of used clothes on social media. The data is processed using Smart PLS version 26. The results of this study indicate that Social Interaction does not affect Purchase Intention, followed by Social Interaction which affects Trust. Consumer involvement has a significant effect on trust, followed by perceived economic benefits which have a significant effect on trust, subjective norms and perceived prices have a significant effect on purchase intention. Meanwhile, Subjective Norm does not affect Purchase Intention. For the moderating effect, trust has a significant effect on purchase intention. Through this research, it is hoped that it can provide a view to the public that selling through live broadcasts is the best marketing system